2015
DOI: 10.1136/jfprhc-2014-101165
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum contraception: a missed opportunity to prevent unintended pregnancy and short inter-pregnancy intervals

Abstract: Almost one in thirteen women in our population presenting for abortion or giving birth has conceived within 1 year of giving birth. Provision of LARC immediately postpartum appears to be an attractive option to mothers, and could be an important strategy to prevent unintended pregnancy and short inter-pregnancy intervals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
102
1
8

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(119 citation statements)
references
References 23 publications
8
102
1
8
Order By: Relevance
“…An interpregnancy interval of less than 12 months increases the risk of preterm birth, low birth weight, stillbirth and neonatal death 1. A 2016 UK study found almost 1 in 13 women presenting for abortion or delivery has conceived within 1 year of giving birth 2. Recent guidance from the Faculty of Sexual & Reproductive Healthcare (FSRH) states that maternity service providers should ensure that all women after pregnancy have access to the full range of effective contraceptive methods and be able to provide these immediately after childbirth,3 but this is not currently routine clinical practice in UK NHS maternity hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…An interpregnancy interval of less than 12 months increases the risk of preterm birth, low birth weight, stillbirth and neonatal death 1. A 2016 UK study found almost 1 in 13 women presenting for abortion or delivery has conceived within 1 year of giving birth 2. Recent guidance from the Faculty of Sexual & Reproductive Healthcare (FSRH) states that maternity service providers should ensure that all women after pregnancy have access to the full range of effective contraceptive methods and be able to provide these immediately after childbirth,3 but this is not currently routine clinical practice in UK NHS maternity hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…The need for a robust postpartum contraception service has been highlighted through research from Edinburgh, where 96.7% of new mothers did not plan to conceive in the first year postpartum and 42.8% would use long-acting reversible contraception (LARC) if it were available before discharge 4. Following this, a pilot postpartum contraception service demonstrated the benefits of antenatal counselling, but also highlighted numerous barriers to providing immediate postpartum contraception 5…”
Section: Introductionmentioning
confidence: 99%
“…Heller et al 1 highlight the potential gap in providing contraception care postpartum. We also saw a missed opportunity to educate postnatal patients about contraception on our wards and to supply such care before discharge.…”
mentioning
confidence: 99%
“…Heller et al 1 found that 43% of the women they surveyed would be prepared to start LARC immediately in the postnatal period. We found that eight women were very likely, three likely and 39 not likely to accept immediate fitting of an intrauterine device/intrauterine system (IUD/IUS).…”
mentioning
confidence: 99%
See 1 more Smart Citation